Analisis Efektifitas Dan Kualitas Pelayanan Ditinjau Perspektif Kepuasan Pada Klinik Mata Utama Tangerang Selatan Tahun 2025 - Elvi Hariyani; Yuni Pratikno; Sri Wahyuningsih (Journal of Innovative and Creativity, 2025)
This study aims to explore patients’ perceptions of healthcare services at Klinik Mata Utama Tangerang Selatan. The clinic serves as a primary and referral eye care facility, playing an important role in supporting the National Health Insurance (JKN) program. Although the clinic operates with a structured system, some patients have expressed a gap between their expectations and the actual services received, particularly in areas such as communication, service flow, and facility comfort. This study employs a qualitative approach using grounded theory as the primary strategy. Ten participants were purposively selected, consisting of active patients who received services at the clinic between January and April 2024. Data were collected through in-depth interviews and analyzed using open coding, axial coding, and selective coding to identify categories and themes that reflect patients’ subjective experiences during their treatment. The results revealed five main themes: the need for clear and understandable information from medical staff, the importance of physical facility comfort in providing a sense of safety and ease, the value of empathetic and responsive service from clinic personnel, uncertainty in service procedures especially for new patients, and expectations for a more orderly and transparent queueing system. The implications of this research highlight the need to improve patient-centered care, particularly in interpersonal communication, streamlined service processes, and the maintenance of patient-friendly facilities. In addition to its practical contribution to clinic management, this study also offers theoretical insights into understanding healthcare service quality from a patient perception perspective through a qualitative approach.